HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DAN KEBUTUHAN AKTUALISASI DIRI PADA REMAJA DI SMA NEGERI 2 DENPASAR - Dewi, Kartika Aprilia; Karin, Putu Ayu Emmy Savitri; Damayanti, Putu Ayu Asri (Coping: Community of Publishing in Nursing, 2024)
Adolescence is a transitional phase from childhood to adulthood, characterized by rapid growth and development in physical, psychological, and intellectual domains. Social media has become a crucial platform for interaction and identity development among adolescents. This study aims to explore the relationship between social media usage intensity and the need for self-actualization among high school students at SMA Negeri 2 Denpasar. Employing a quantitative approach with a cross-sectional design, the study collected data from 105 students using the Social Networking Time Use Scale (SONTUS) and Personal Orientation Inventory (POI). The results of univariate analysis based on age showed that the majority of respondents were 16 years old, which amounted to 37.1%. Most of the respondents were female, which amounted to 55.25%. The most popular social media platform among respondents was TikTok, with 83.8% using it..The results indicate a significant positive correlation between social media usage intensity and the level of self-actualization among adolescents, with a correlation coefficient of 0.633 (p < 0.001). The study is expected to provide valuable information for future researchers and insights for parents and educators to understand the impact of social media on adolescent development.